2019
DOI: 10.12659/msm.919316
|View full text |Cite
|
Sign up to set email alerts
|

Concentrated Growth Factor Promotes Dental Pulp Cells Proliferation and Mineralization and Facilitates Recovery of Dental Pulp Tissue

Abstract: Background: Dental pulp cells (DPCs) play vital roles in the recovery of dental pulp tissue. Concentrated growth factor (CGF) can promote proliferation and mineralization of various cells. However, the functions of CGF on DPCs and dental pulp tissue are unclear. The object of our study was to identify the roles of CGF in DPCs proliferation and mineralization in vitro and to assess the effects of CGF on direct pulp capping in vivo. Material/Methods: We performed CCK-8 and Transwell assay to detect proliferation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
29
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(30 citation statements)
references
References 38 publications
1
29
0
Order By: Relevance
“…Stimulation of the cells with either adiponectin or leptin in a time-dependent manner increased the proliferation index of the cells as measured by BrdU incorporation, and both proteins show the same effects on human osteoblast cell proliferation [23] [24]. Conversely, stimulated pulp cells showed no change in ALP activity compared to control cells and showed no expression of Runx2 [20] [25] [26]. ALP activity and the expression of Runx2 were promoted by activated osteoblasts, so isolated pulp cells in this study might not be induced to differentiate into the calcification cells [19].…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…Stimulation of the cells with either adiponectin or leptin in a time-dependent manner increased the proliferation index of the cells as measured by BrdU incorporation, and both proteins show the same effects on human osteoblast cell proliferation [23] [24]. Conversely, stimulated pulp cells showed no change in ALP activity compared to control cells and showed no expression of Runx2 [20] [25] [26]. ALP activity and the expression of Runx2 were promoted by activated osteoblasts, so isolated pulp cells in this study might not be induced to differentiate into the calcification cells [19].…”
Section: Discussionmentioning
confidence: 95%
“…Passive calcification and fibril hyperplasia are usually observed among the aging in pulp tissue. However, these changes are found not only in teeth affected by occlusion, mastication, caries, or hypersensitivity, but also in unerupted teeth, and it is inferred that pulp cells are affected under these conditions [18] [19] [20]. Additionally, osteoblasts and osteoclasts are also regulated by adipokines, which promote bone metabolism [10] [12] [21].…”
Section: Discussionmentioning
confidence: 99%
“… The secretion of TNF-α and IL-8 in DPSCs treated by CGF could promote the DPSCs migration. Tian et al (2019) [ 36 ] h-DPSCs Proliferation, migration, and odonto/osteogenic differentiation Cell counting kit-8; Transwell assays; ALP activity, ARS, and qPCR (DMP-1, DSPP, BSP, RUNX2) CGF promoted the proliferation and migration of DPSCs in a dose-dependent manner, and CGF enhanced DPSCs odonto/osteogenic differentiation by upregulating RUNX2 transcription. BMP-2/SMAD5/Runx2 signaling axis is related to CGF-mediated DPSCs mineralization.…”
Section: Effects Of Cgf On Scs In Dpc Regenerationmentioning
confidence: 99%
“…CGF is known to stimulate the proliferation of various MSC types (e.g., PDLSCs, DPSCs, and MSCs [hTERT-E6/E7]) in a dose-dependent manner, possibly through the independent or synergistic effects of GFs [ 36 , 37 , 40 , 42 ]. However, some studies have reported a lack of dose dependence, which may be attributable to the different methods used to prepare CGF [ 34 , 38 ].…”
Section: Effects Of Cgf On Scs In Dpc Regenerationmentioning
confidence: 99%
See 1 more Smart Citation